Differential biomechanical responses of elastic and muscular arteries to angiotensin II-induced hypertension. (15th April 2021) - Murtada, S.-I.; Kawamura, Y.; Weiss, D.; Humphrey, J.D.
Abstract: Elastic and muscular arteries are distinguished by their distinct microstructures, biomechanical properties, and smooth muscle cell contractile functions. They also exhibit differential remodeling in aging and hypertension. Although regional differences in biomechanical properties have been compared, few studies have quantified biaxial differences in response to hypertension. Here, we contrast passive and active changes in large elastic and medium- and small-sized muscular arteries in adult mice in response to chronic infusion of angiotensin over 14 days. We found a significant increase in wall thickness, both medial and adventitial, in the descending thoracic aorta that associated with trends of an increased collagen:elastin ratio. There was adventitial thickening in the small-sized mesenteric artery, but also significant changes in elastic lamellar structure and contractility. An increased contractile response to phenylephrine coupled with a reduced vasodilatory response to acetylcholine in the mesenteric artery suggested an increased contractile state in response to hypertension. Overall reductions in the calculated gradients in pulse wave velocity and elastin energy storage capability from elastic-to-muscular arteries suggested a possible transfer of excessive pulsatile energy into the small-sized muscular arteries resulting in significant functional consequences in response to hypertension.